Aesthetics-based development of green open space using the SBE–AHP approach to support user experience and social interaction - Rian Palimirmo Adi; Mahawan Karuniasa; Rudy Parluhutan Tambunan (Journal of Placemaking and Streetscape Design, 2026)
Background:  Over the past two decades, rapid urbanization in Jakarta has increased by 19%, contributing significantly to urban environmental degradation. The North Kembangan Urban Forest represents one of the green open spaces intended to support environmental improvement in urban planning. However, its management and aesthetic value remain suboptimal. Aligning with an emerging placemaking perspective that emphasizes user experience and place quality, enhancing aesthetic value offers a viable solution to improve green open space (GOS) quality by integrating public perception and expert assessment. Methods: This study utilized a questionnaire survey, a Scenic Beauty Estimation (SBE) analysis involving public respondents, and an Analytical Hierarchy Process (AHP) involving experts. Findings: The results indicated that photos 5, 7, and 10 received the highest scores, falling within the moderate aesthetic category. There was a significant relationship between color scores, vegetation scores, neatness scores, and comfort scores and aesthetic value, with neatness and comfort identified as the most influential parameters. The High-Canopy Tropical GOS was identified as the preferred development alternative, with the highest priority weight of 0.41. Conclusion: These findings highlight the importance of integrating ecological, economic, social aspects, and aesthetic value in GOS planning, particularly in the North Kembangan Urban Forest to create meaningful, engaging, and user-oriented public spaces. Novelty/Originality of this article: This study contributes a novel, integrated approach by combining public aesthetic perception with expert-based multi-criteria decision-making. This synthesis results in an aesthetic-driven GOS model underpinned by an environmental science perspective, and contributes to the development of urban GOS planning which is user-centered and place-oriented.